IL-17 in Protective Immunity to Vaginal Candidiasis - Baghdad Science Journal (مجلة بغداد للعلوم)
Vulvovaginal candidiasis (VVC) is caused by Candida albicans affects a significant number of women during their reproductive ages. Th17 cells play a major role in coordinating the host defense in oropharyngeal candidiasis. In this study we investigated the involvement of the Th17 response in an animal model of vulvovaginal candidiasis (VVC). The present study aimed to shed light on detect concentration of the IL-17 of infected animal and control . A direct Enzyme Linked Immunosorbent Assay (ELISA) was used to quantify IL-17 concentrations in 30 infected animal with VVC and 10 control group. Rats were intravaginally inoculated with C.albicans, and vaginal lavage fluids, serum were evaluated for proinflammatory cytokine IL-17 The data suggest that IL-17, produced by vaginal cells, particularly CD4 T cells, detected in the vaginal wash and serum during the infection, reaching a maximum 14 days after the challenge.